Representasi Hobi Pecinta Burung dalam Lagu “Kicau Mania”: Kajian Semiotika - Ingghar Ghupti Nadia Kusmiaji; Talitha Afifah; Aris Fatunnisa; Intan Agustina Likabella Putri; Putri Naza Anggun; Laura Mirpana Rohmah (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to describe the representation of bird lovers' hobbies in the lyrics of the song "Kicau Mania" popularized by Ndarboy Genk together with Banditoz Yaow 86 through the semiotic analysis of Ferdinand de Saussure. The study employs a descriptive qualitative approach with data sources in the form of song lyrics analyzed using the concepts of signifier and signified. Data collection techniques were carried out through listening and note-taking techniques, while data analysis was conducted by identifying semiotic signs in the song lyrics and then interpreting the denotative and connotative meanings contained within them. The results show that the song represents bird lovers' activities as a form of affection and responsibility toward pet birds, inner peace and harmony of life, community solidarity and collective identity, sportsmanship and moral values, as well as achievement and self-esteem. Furthermore, the song describes the kicau mania culture as a social phenomenon that strengthens relationships among people through shared hobbies that transcend geographical and social boundaries. Thus, song lyrics not only function as a medium of entertainment but also as a representation of culture and social life that reflects universal human values. This research contributes to the development of semiotic studies, cultural linguistics, and popular media analysis based on local communities in Indonesia